Asian Servants for the Imperial Telegraph: Imagining North Australia as an Indian Ocean Colony before 1914. Issue 2 (3rd April 2017) - Martı́nez, Julia
Abstract : In the late nineteenth century, the officers of the Eastern Extension Australasia and China Telegraph Company provided north Australia with a cable connection to London via Java, Singapore, and India. The telegraph project prompted a new era of colonisation in tropical north Australia and the officers of the company sought to ensure that the north would be shaped according to their notions of Indian Ocean colonial culture. They insisted on employing Asian domestic servants in opposition to White Australian nationalists who advocated restrictions on Asian migration. Like the pearling industry, which was permitted ongoing access to Asian labour, the telegraph company drew on the support of liberal parliamentarians, and leveraged their privileged position as providers of imperial telecommunications to develop an elite colonial counter-culture in north Australia.